Research progress of hepatocyte nuclear factor 4α in gastric cancer and precancerous lesions - YANG Yuyan, ZHAO Weihan, WANG Siyu, DONG Siqi (Zhongguo linchuang yanjiu)
Hepatocyte nuclear factor 4α (HNF4α) is a member of the nuclear receptor superfamily, a kind of protein that binds to a specific gene promoter. It controls the expression of functional genes and is also involved in the regulation of many cellular processes, and is one of the key factors for the development of human tissues and organs. A large amount of evidences have shown that abnormal expression of HNF4α is related to the proliferation, differentiation, progression and metastasis of cancer cells. In recent years, more and more studies have confirmed that HNF4α can participate in the process of gastric cancer and precancerous lesions through multiple pathways, and has been proved to be an oncogene in gastric cancer. This article summarizes the role of HNF4α in the development and progression of gastric cancer and precancerous lesion, and reviews the potential clinical applications of HNF4α as a biomarker and therapeutic target for gastric cancer, in order to provide new ideas for the development of novel drugs for gastric cancer and precancerous lesions.